Venture Capital and Economic Growth: An Industry Overview and Singapore's Experience - KOH, Francis (Institutional Knowledge at Singapore Management University, 2002)
This paper provides an overview of the venture capital industry, and its development in Asia and Singapore. Venture capital plays an important role in innovation and economic growth. Indeed, the resurgence of the United States as a technology leader is intimately linked to the success of Silicon Valley. As Singapore enters the next phase of economic development, the creation of internal engines of growth is an urgent task. The Singapore government has done much to provide an environment for entrepreneurship to thrive. Its success at replicating the Silicon Valley culture will be important for Singapore’s future economic success.